To Post or Not to Post? Perceptions of the Use of a Closed Facebook Group as a Networked Public Space. Issue 1 (2nd January 2017) - Ballantyne, Neil; Lowe, Simon; Beddoe, Liz
ABSTRACT: Members of a closed Facebook group, established to discuss professional social work issues, were surveyed to explore what they valued about the group, the problems or issues associated with membership, and factors associated with participation or reluctance to participate. A non-probability, self-selection sample ( N  = 53) completed an online survey during January and February 2016. Survey findings suggest that participants valued feeling connected to a community of practice, the ability to post and share information, and access to news and information. However, participants also expressed concern about online incivility and experienced reluctance to post opinions because of concerns about the critical comments of others.